Geological Reconnaissance along the Alaska Highway from Fort Nelson, British Columbia, to Watson Lake, Yukon: - Williams, M.Y (Author); Geological Survey of Canada (Author) (Geological Survey of Canada, 1944)
by M. Y. Williams. Paper (Geological Survey of Canada) 44-28.